2010
DOI: 10.1007/s12529-010-9136-3
|View full text |Cite
|
Sign up to set email alerts
|

Social Support and Optimism in Relation to the Oral Health of Young Adults

Abstract: Social support and optimism were associated with oral health. Impact of dental problems showed buffering of high support when optimism was low, and high optimism when support was low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 21 publications
(23 reference statements)
1
14
0
3
Order By: Relevance
“…We identified 21 studies that reported positive associations between at least one individual‐level measure of social capital (or related concepts) and better oral health outcomes among adults. Outcomes included number of remaining teeth, edentulism, dental visits, and denture status among older people , dental caries , self‐rated oral health , oral health‐related quality of life , periodontal disease , and dental pain .…”
Section: Social Capital and Health – Evidence From Empirical Researchmentioning
confidence: 99%
“…We identified 21 studies that reported positive associations between at least one individual‐level measure of social capital (or related concepts) and better oral health outcomes among adults. Outcomes included number of remaining teeth, edentulism, dental visits, and denture status among older people , dental caries , self‐rated oral health , oral health‐related quality of life , periodontal disease , and dental pain .…”
Section: Social Capital and Health – Evidence From Empirical Researchmentioning
confidence: 99%
“…Currently, some internally psychological constructs have been given increasing attention in research on the potential resources of OHRQoL with the rise of positive psychology [ 17 , 20 , 21 ]. General self-efficacy refers to a relatively stable belief in personal competence to deal with various stressful situations effectively [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…En adolecentes, según el estudio realizado por Mashoto, la historia de caries alteraría la calidad de vida debido al dolor dental y a la dificultad para comer y lavarse los dientes (20) . En adultos, Gomes determina que los niveles de COPD están directamente relacionados a niveles de impacto físico, psicológico y social en el desempeño diario de los individuos (23) y Brennan concluye que altos niveles de optimismo están relacionados con la disminución del impacto de problemas dentales y menor pérdida de piezas dentarias (10) . Hasta el momento, todos los estudios utilizan instrumentos validados de CVRSO que no son específicos para caries dental, por otro lado, a mayor edad de los individuos tendrán mayor cantidad de patologías orales simultáneas por lo que discriminar cual de todas éstas es la que está causando mayor detrimento de la calidad de vida representa una dificultad.…”
Section: Discussionunclassified
“…Con respecto al diseño de estos, 4 eran estudios transversales (9,20,23,25) y 2 de casos y controles (10,15) . 3 de los estudios estaban enfocados a la población pediátrica entre 4 y 5 años de edad (9,15,25) , un estudio a adolescentes con un promedio de edad de 13.8 años (20) y dos estudios de población adulta (10,23) .…”
Section: Estrategia De Búsqueda Y Selección De Artículos (Figura 1)unclassified
See 1 more Smart Citation